Reporte de Caso Clínico en Paciente Canino con Tumor Laríngeo, Durante el Desarrollo de Pasantía en una Clínica Veterinaria en la Ciudad de Bogotá. (2023)
Laryngeal neoplasms are uncommon in dogs. However, these tumors can trigger numerous progressive clinical signs related to respiratory distress and impaired speech. The diagnosis of laryngeal cancer should be made based on the patient's history and symptoms, combined with complementary tests.